Infrared live imaging and navigated laser for nematode photocoagulation in a child with diffuse unilateral subacute neuroretinitis (DUSN) - Christof Hänsli; Cornelia Staehelin; Alexandra Bograd; Christoph Tappeiner (American Journal of Ophthalmology Case Reports)
Purpose: To report the application of an infrared fundus imaging and navigated laser system to photocoagulate a nematode in diffuse unilateral subacute neuroretinitis (DUSN). Observations: A 14-year-old boy with DUSN was treated with systemic albendazole and corticosteroids. Laser photocoagulation of the visible nematode was performed using a navigated laser in live infrared fundus view (Navilas 577s, OD-OS GmbH, Berlin, Germany). While the localization of the nematode was difficult in regular fundoscopy due to the light-shy helminth, it could be well localized and targeted with the infrared live video mode and navigated laser system. No inflammatory flare-up was observed after the nematode was killed. Conclusions and Importance: Laser photocoagulation and systemic antihelminthic therapy are an established treatment for DUSN. Infrared imaging and navigated laser systems seem useful in targeting and killing mobile nematodes.